RELATIONSHIP OF NUTRITIONAL INTAKE OF BREAST MILK AND HYPERBILIRUBIN IN PREMATURES - riska aprilia wardani; Bety Maya Sari; Dian Fitra Arismawati (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
ABSTRACT Almost all premature babies have hyperbilirubin due to immature body organs and liver function. Breast milk nutrition, which is often found, especially colostrum, can stimulate the baby's bowel movements to help the excretion process through the feces so that it will clear meconium faster, this will help remove bilirubin in the baby's body. The aim of this study was to analyze the relationship between breastfeeding nutrition and the incidence of hyperbilirubin in premature babies in the NICU room of the Wahidin Soedirohusada Regional Hospital, Mojokerto. This type of research is analytic with cross sectional approach. The population of all preterm infants treated in the NICU room of the Wahidin Soedirohusada Mojokerto Regional Hospital was 24 respondents with a total sample of 20 respondents with consecutive sampling. This research was started on March 10 - April 9 2019. Data collection was done by observing drinking intake and observing laboratory results, with 2 independent and dependent variables. Data analysis by editing, coding, scoring, tabulating, chi square test. Furthermore, statistically tested using the chi square test using the SPSS windows program with a significance limit (ά = 0.05) H1 is accepted and H0 is rejected if ρ <0.05. Based on the results of the research, some respondents, namely 11 respondents (55.0%) experienced good breastfeeding nutrition and there were no hyperbilirubin 12 respondents (60%) of 20 respondents who had good breastfeeding nutrition and did not occur hyperbilirubin as many as 10 respondents (50%) with chi square test, the value of ρ is 0.008, where ρ = 0.008 <0.05, then H1 is accepted. There is a relationship between breastfeeding nutrition and the incidence of hyperbilirubin in premature babies in the NICU room of the Wahidin Soedirohusada Regional Umun Hospital, Mojokerto. The results of the study are expected for the hospital to increase education about the benefits of breastfeeding to prevent hyperbilirubin and to hold a breastfeeding corner.